O efeito de dois tipos de treinamento físico em ratas idosas tratadas ou não com estrógeno - Severi, Maria Theresa Munhoz (2013)
The literature presents many alternatives of physical training and frequently reiterates the use of animal models for studies on the effect of training, as the results in animals are similar to those in humans. There is also the possibility of evaluating variables such as volume and intensity. In addition, many studies have reported beneficial effects of estrogen as an important resource to minimize the deleterious effects of aging. As a means of understanding estrogen action and its influence on aerobic and anaerobic exercise, four experiments were carried out in this context. The first study was called The behavior of glycogen reserves in female rats denervated muscle, with different doses of estrogen and aimed at evaluating the estrogen action on the glycogenic profiles of denervated skeletal muscle.Methods: The animals were divided in 6 experimental groups (n=6): control (C), denervated for 15 days (D), denervated and treated with estrogen 20mg/weight/day (E20), denervated and treated with estrogen 40mg/weight/day (E40), denervated and treated with estrogen 80mg/weight/day (E80) and denervated and treated with estrogen 160mg/weight/day (E160). The treatment was realized by 15 days and the choice substance was estradiol cipionate. The following analyses were carried out: glycogen reserves in soleus (S), white (WG) and red gastrocnemius (RG), body and soleus weights. The statistical analysis included the Kolmogorov-Smirnov test, ANOVA and post-hoc Tukey test (p<0.05). Results: The denervation induced a reduction in glycogen content in the S, WG and RG muscles. The groups treated with estrogen we observed a progressive elevation in glycogen reserves concomitant with the elevation of dose and reinstate the glycogen reserves, but the dose that shows a better action is 160mg/weight/day were we observed the greatest quimiometabolic responses. Conclusions: These results suggest that estrogen may be an effective resource to minimize the metabolic compromising that follows the skeletal muscle atrophy induced by denervation. Subsequently, we conducted a study called Estrogen modulation of insulin secretion in isolated rat pancreatic islets , whose goal was to evaluate the sensitivity to glucose in pancreatic islets isolated from female rats treated with estradiol cypionate (160 mg/body weight/ 15 days) as well as its effect on concentration of protein kinase C and protein kinase A in isolated islets. For this purpose, islets were isolated from rats by the collagenase method to evaluate the secretory process in the presence of different concentrations of glucose. On the other hand, the concentration of the enzymes PKC and PKA was also performed by Western blotting. Statistical analysis was applied to normality test (Kolmogorov-Smirnov test) followed by Tukey test, p <0.05. The results showed that the group treated with estradiol cypionate had greater insulin secretion against the same concentration of glucose, and increase of concentration of PKA and PKC enzymes, compared to control. The results show insulinotropic properties of estrogen in synergy with glucose, which is the main insulin secretagogue, since the hormone did not alter the secretion at concentrations normoglycaemia. Possibly the focus of the secretagogue action of estrogen involves the activation of cytosolic enzyme pathways that determine the exudation of insulin. From these observations, we conducted the third study entitled "Electrocardiographic profile of aged rats trained and treated with estrogen , whose goal was to assess the eletrocardiographic profile of rats treated with the association of estrogen and physical activity. We used Wistar rats at 1 year of age, which were submitted to two programs of aerobic exercise (swimming 3 sessions weekly / 8 weeks) and anaerobic (climbing stairs of 80 cm, 3 sessions weekly / 8 weeks). We evaluated blood pressure and ECG intervals considering the QRS, QTc and PR. Data were compared by Student's t test followed by Tukey test, p <0.05. The findings of this study showed that the group treated with estrogen values were 21% lower compared to the control group. With respect to training, we observed that aerobic training promoted 25% reduction in FC, which reached 37.2% reduction in the presence of estrogen. In anaerobic training, we observed 28% reduction, which was accentuated to 40% when estrogen was present. Thus we conclude that treatment with estrogen alone or associated with physical activity was effective in maintaining and improving conditions in the metabolic and functional heart in the cardiac changes that accompany the aging process. Subsequently, we held the fourth paper entitled "Metabolic actions of estrogen in rats subjected to two types of physical training . The purpose of this study was to evaluate whether rats supplemented with estrogen show better responses to the aerobic and anaerobic physical activity. We used aged Wistar rats (13 months), placed under ideal conditions of bioterism and divided into experimental groups called Control and Treated with estrogen (E, 160μg/100g), Aerobically and Anaerobically trained, and Treated with estrogen or not. Blood samples were collected for biochemical evaluation and samples of different muscles of the anterior and posterior were collected for glycogen content assessment by the phenol sulfuric method. The outcomes show that both estrogen and the different workout programs promoted increase in muscle glycogen reserves. Besides, the association of hormone with exercise promoted an additional effect with further enhances in energy conditions. Additionally, we found lower plasma free fatty acids and abdominal fat, and there was also an increase in total protein concentration indicating adjustments in metabolic homeostasis, an important condition to be preserved in the aging process.